2014
DOI: 10.2478/s11756-014-0361-0
|View full text |Cite
|
Sign up to set email alerts
|

Spatial structure of eukaryotic ultraplankton community in the northern South China Sea

Abstract: Spatial distribution, diversity and composition of eukaryotic ultraplankton community of the northern South China Sea (nSCS) surface water and the relationship with the in situ water environment were investigated by the method of polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE). A total of 18 DGGE intensive bands were detected and the sequence analysis of these DGGE bands revealed that Alveolata was the dominant eukaryotic ultraplankton group of surface water in the nSCS (50%). Othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 51 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have been done on prokaryotes and viruses, including their biodiversity distribution and community response to environmental factors in the Pearl River Estuary (PRE) and the SCS [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. In terms of protists, several pioneering studies have shown that protists have high diversity in the PRE [ 52 , 53 , 54 ] and the northern/central SCS [ 24 , 55 , 56 ], and protistan communities are constrained by complex environmental factors [ 57 , 58 , 59 ]. However, the composition and assembly processes of the active protistan assemblages along the PRE to the SCS basin transect and the driving factors of the total and abundant/rare taxa need further exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have been done on prokaryotes and viruses, including their biodiversity distribution and community response to environmental factors in the Pearl River Estuary (PRE) and the SCS [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. In terms of protists, several pioneering studies have shown that protists have high diversity in the PRE [ 52 , 53 , 54 ] and the northern/central SCS [ 24 , 55 , 56 ], and protistan communities are constrained by complex environmental factors [ 57 , 58 , 59 ]. However, the composition and assembly processes of the active protistan assemblages along the PRE to the SCS basin transect and the driving factors of the total and abundant/rare taxa need further exploration.…”
Section: Introductionmentioning
confidence: 99%